2017
DOI: 10.1002/pbc.26453
|View full text |Cite
|
Sign up to set email alerts
|

The use of intravenous pentamidine for the prophylaxis of Pneumocystis pneumonia in pediatric patients

Abstract: Pneumocystis jiroveci pneumonia was common in the immunocompromised host before the widespread use of prophylaxis. When trimethoprim-sulfamethoxazole is not tolerated, prophylaxis with intravenous pentamidine (IVP) may be initiated. We performed a retrospective analysis of all pediatric patients who received IVP regarding efficacy, safety, and reason for initiation. Of 106 patients included in our analysis, one patient tested positive for Pneumocystis DNA. Adverse events were reported in 18% of IVP courses, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…Recent studies have reported acceptable breakthrough PCP rates (0% to 1.3%) with the use of i.v. pentamidine for PCP prophylaxis in immunocompromised children receiving chemotherapy or status post hematopoietic stem cell transplant (HSCT) or solid organ transplant (SOT) (10,14,15).…”
mentioning
confidence: 99%
“…Recent studies have reported acceptable breakthrough PCP rates (0% to 1.3%) with the use of i.v. pentamidine for PCP prophylaxis in immunocompromised children receiving chemotherapy or status post hematopoietic stem cell transplant (HSCT) or solid organ transplant (SOT) (10,14,15).…”
mentioning
confidence: 99%
“…We are writing you with regards to the brief report, “The use of intravenous pentamidine for the prophylaxis of Pneumocystis pneumonia in pediatric patients,” published in January 2017 …”
mentioning
confidence: 99%
“…While TMP–SMX remains the gold standard for PJP prophylaxis, bone marrow toxicity is a limiting factor for its use in pediatric patients receiving tandem ASCT, who require adequate hematologic recovery between them. American and European guidelines suggest second‐line drugs such as inhaled pentamidine, dapsone, or atovaquone, with limited evidence . Some practicalities should be considered, related to equipment and facilities that may make using inhaled pentamidine difficult …”
mentioning
confidence: 99%
See 2 more Smart Citations